2022
DOI: 10.3390/nu14132657
|View full text |Cite
|
Sign up to set email alerts
|

Skipping Breakfast and Incidence of Frequent Alcohol Drinking in University Students in Japan: A Retrospective Cohort Study

Abstract: Frequency of alcohol drinking is a potential predictor of binge drinking of alcohol, a serious social problem for university students. Although previous studies have identified skipping breakfast as a predictor of various health-compromising behaviors and cardiometabolic diseases, few studies have assessed the association between skipping breakfast and the incidence of frequent alcohol drinking. This retrospective cohort study included 17,380 male and 8799 female university students aged 18–22 years admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…There is strong evidence of an association between breakfast skipping and overweight/obesity [ 48 ], but in this study, there was a lack of association between overweight/obesity and skipping breakfast. In a cross-sectional study, students who skipped breakfast were more vulnerable to alcohol consumption and its toxic effects [ 58 ]. Furthermore, in this study, a lack of a significant association was observed between both unhealthy habits.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence of an association between breakfast skipping and overweight/obesity [ 48 ], but in this study, there was a lack of association between overweight/obesity and skipping breakfast. In a cross-sectional study, students who skipped breakfast were more vulnerable to alcohol consumption and its toxic effects [ 58 ]. Furthermore, in this study, a lack of a significant association was observed between both unhealthy habits.…”
Section: Discussionmentioning
confidence: 99%
“…Eligible participants of this retrospective cohort study were 20,659 university students enrolled at Osaka University between 2010 and 2015. The study protocol was described in detail elsewhere 9 (Supplementary Materials). Briefly, this study included 17,774 (86.0%) university students after excluding 106 (0.5%) students aged ≤17 and ≥23 years, 19 (0.1%) students with baseline alcohol consumption frequency of ≥4 days/week, 814 (3.9%) students with missing baseline data, and 1,946 (9.4%) students with no measurement of alcohol consumption frequency at annual health checkups over the 6-year observational periods after their baseline checkups (Figure S1).…”
Section: Methodsmentioning
confidence: 99%